2018
DOI: 10.1002/mmce.21403
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized frequency-agile bandpass filter integrated single-pole double-throw switch

Abstract: This article presents a miniaturized frequency‐agile bandpass filter (BPF) integrated single pole double throw (SPDT) switch using common LC resonator. The BPF‐integrated on‐sate channel is constituted by the capacitively coupled LC resonators with loaded varactor diodes and reverse‐biased p‐i‐n diodes. The off‐state channel with high suppression is built when the p‐i‐n diodes loaded LC resonators is forward‐biased. As an example, a frequency‐agile BPF‐integrated SPDT switch with constant 3‐dB fractional bandw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…The comparison of the proposed filtering switch with previous prototypes is outlined in Table 2. As compared with the reported PCB filtering switches, [2][3][4][5][6][7][8] the proposed one features much smaller in-band insertion loss and better in-band return loss. Although the in-band insertion loss of the proposed filtering switch is at the same level as the DR or CR ones, 9,10 it features lighter weight because no metal cavity is engaged.…”
Section: Experiments Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The comparison of the proposed filtering switch with previous prototypes is outlined in Table 2. As compared with the reported PCB filtering switches, [2][3][4][5][6][7][8] the proposed one features much smaller in-band insertion loss and better in-band return loss. Although the in-band insertion loss of the proposed filtering switch is at the same level as the DR or CR ones, 9,10 it features lighter weight because no metal cavity is engaged.…”
Section: Experiments Results and Discussionmentioning
confidence: 94%
“…Therefore, co-designs of switch and filter, namely switchable filter or filtering switch, have been presented by researchers. Lots of single-band [2][3][4][5] or dual-band [6][7][8] filtering switches have been designed based on the microstrip resonators by using the printed circuit board (PCB) technology. Their planar structures were convenient for integration and featured the advantages of light weight.…”
Section: Introductionmentioning
confidence: 99%
“…Filter-integrated switch (FIS) as depicted in Figure 1 is another integrated/multifunction device. From the year 2006 onwards, numerous studies have reported filter-integrated double pole double throw (DPDT) switch [5], single pole single throw (SPST) switch [6][7][8], and SPDT switch [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. In order to produce FISs and integrate BPF with SPDT switch in one device, several techniques have been used, such as dielectric resonators (DRs) [15], LC resonators [11], substrate integrated suspended line (SISL) [30], and common shorted stepped-impedance resonator (CSSIR) [25].…”
Section: Introductionmentioning
confidence: 99%
“…From the year 2016 onwards, numerous studies have reported on filterintegrated single pole hepta throw (SP7T) switch, 6 single pole quad throw (SPST) switch 7,8 and SPDT switch. [7][8][9][10][11][12][13][14][15][16][17][18] In order to produce FISs and integrate band-pass filter (BPF) with SPDT switch in one device, several techniques have been used, such as dielectric resonators (DRs), LC resonators, substrate integrated suspended line (SISL) and common shorted stepped-impedance resonator (CSSIR).…”
Section: Introductionmentioning
confidence: 99%